Pengaruh Faktor Lingkungan terhadap Strategi dan Kinerja Industri Manufaktur di Jawa Timur - Rachmad Hidayat; Hairil Budiarto (Semesta Teknika, 2009)
This research examined the influence of environment factors (industrial, operational and remote) on the strategy and performance of manufacturing industries in East Java. The Structural Equation Modeling (SEM) was employed to test the hypotheses which emerged from the observed conditions. Moreover, the AMOS 4.0 was also used to perform the SEM. The results showed that the environment factors, i.e. industrial and operational environments as well as remote environments jointly affect the understanding of the environment industry matching with industry and environmental operational environment to establish its strategic objectives as an effort to achieve optimum performance manufacturing industries in East Java. Industrial environment conditions cannot be isolated from the global crisis because most industries prefer to concentric diversification strategy where new product technologies have a relevance to existing products.